Efficacy of Chest Physiotherapy and Incentive Spirometry on Pulmonary Function in Post operative Period after Abdominal Surgery; A Comparative Study - Singh, Dr. Khileshwar; Sudheer, Dr. D.; Dwivedi, Dr. S. K.; Goyal, Dr. Manish (International Journal of Innovative Research in Medical Science, 2017)
Objective: To study effect of chest physiotherapy and incentive spirometry on pulmonary functional performances in patients who underwent laparoscopic surgery. Materials & Methods: 120 patients, who underwent laparoscopic surgery, were randomly divided as follows; 80 subjects performed chest physiotherapy & incentive spirometry and 40 participated as a control group. Both the group was comparable with age, sex, height, weight etc. Smokers and subjects who had previous lung diseases were excluded from the study. Both groups underwent pulmonary function test with measurement of FVC, FEV 1, MVV & PEFR and compared. Result: Patients who got chest physiotherapy and incentive spirometry have better lung function value, less chest infection and faster recovery than control group in post operative period. Conclusion: This study concluded that chest physiotherapy with incentive spirometry showed significant improvement in FVC, FEV1, and MVV & PEFR and reduced post operative pulmonary complications in the exercise patients compared to control patients.